Interventionist, Non-Interventionist, or Interactionist: Investigating Teacher Beliefs and Classroom Management in Indonesian EFL Contexts - Novika Amalia (Edulitics (Education, Literature, and Linguistics) Journal, 2025)
Teachers’ beliefs about classroom management and pedagogical practices can generally be categorized into interventionist, non-interventionist, or interactionist approaches, which describe how teachers design learning environments, manage student behavior, and implement instructional strategies. This study investigates the relationship between teachers’ beliefs and pedagogical practices in Indonesian EFL Senior High Schools, focusing on their alignment and the factors shaping their decisions. This qualitative, multiple-case study explored the perspectives of two certified English teachers with differing levels of congruency between their stated beliefs and observed practices. Data were collected through semi-structured interviews, analyzed thematically, and validated through peer reviews, expert validation, and member checking to ensure accuracy and reliability. Findings revealed five key factors influencing teachers’ pedagogical decisions: students’ academic competence, psychological well-being, future objectives, learning competence, and school-provided learning facilities. Results indicate that Teacher A initially held an interventionist belief but exhibited an interactionist teaching style due to classroom challenges that reshaped her perceptions. Conversely, Teacher B maintained a strong interventionist approach, making only minor adjustments based on student feedback and professional development experiences. Despite their differing levels of congruency, both teachers expressed satisfaction with their teaching practices. This study concludes that teacher effectiveness in Indonesian EFL classrooms depends more on adaptability and student needs than strict alignment between beliefs and practices. These findings contribute to the discourse on teacher belief systems, pedagogical adaptability, and classroom management strategies in EFL contexts, highlighting the dynamic nature of teachers' professional growth and instructional decision-making.